FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MEROKOK SISWA KELAS VII MTS TPI SILAU DUNIA KECAMATAN SILAU KAHEAN KABUPATEN SIMALUNGUN - M Dasril Samura (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2023)
Abstract Smoking behavior is a common phenomenon in Indonesian society. Currently smoking has penetrated into the lives of school children starting from high school, junior high school and even some elementary school children have smoked. The prevalence rate of adolescent smokers in North Sumatra Province at the age of 10-19 years is 27.28% of the total population. There are many factors that influence smoking habits among students, including the influence of the parents' environment, the influence of friends, personality factors and because of advertising. This research was conducted at MTS TPI Silau Dunia, Silau Kahean District, Simalungun Regency. This type of research is a quantitative study using a cross sectional. The population determined in this study were all seventh grade students of MTS TPI Silau Dunia. The number of available samples is 58 samples taken by purposive sampling from the population. The results of the bivariate analysis of the influence of knowledge, attitudes, parental control, and peers on smoking behavior obtained p-values of 0.002, 0.001, 0.001, and 0.002, respectively. From the results of the bivariate analysis of p value < (0.05), it can be concluded that there is an influence of knowledge, attitudes, parental control, and peers on the smoking behavior of seventh grade students of MTS TPI Silau Dunia, Silau Kahean District, Simalungun Regency. The need for education from MTS TPI Silau Dunia about substances in cigarettes and the dangers of smoking to health as well as monitoring student behavior, especially students who already smoke.